Genetic Predictors of Benign Course of Ulcerative Colitis—A North American Inflammatory Bowel Disease Genetics Consortium Study. Issue 10 (October 2016) - Kopylov, Uri; Boucher, Gabrielle; Waterman, Matti; Rivers, Claudia R.; Patel, Mohini; Cho, Judy H.; Colombel, Jean F.; Duerr, Richard H.; Binion, David; McGovern, Dermot P. B.; Schumm, Phillip P.; Brant, Steven R.; et al.
Abstract : Background: A subset of patients with ulcerative colitis (UC) have a benign course and an overall favorable prognosis. Early identification of these low-risk patients may allow for a less aggressive therapeutic approach and possible reduction of therapy-associated risks. The aim of this project was to identify the genetic predictors of benign UC phenotype. Methods: UC patients were selected from the National Institute of Diabetes and Digestive and Kidney Diseases Inflammatory Bowel Disease Genetics Consortium. Benign phenotype was defined as no need for immunomodulatory or biological therapy, hospitalizations, or colectomy. The association between benign UC phenotype and known loci linked to the risk of inflammatory bowel disease (IBD) was evaluated. The results for 156 index single-nucleotide polymorphisms (SNPs) from the known IBD loci were extracted for the main analysis. The association of the benign phenotype to a genetic burden score was also evaluated. Results: None of the index SNPs from the IBD loci reached the predefined threshold of 1 × 10 −4 . In the exploratory analysis of the remaining Immunochip SNPs and imputed major histocompatibility complex data, 5 distinct suggestive association signals are identified (rs1697950, rs2523639, rs17836409, rs11742854, and rs75001121). Conclusions: No SNPs from IBD susceptibility loci were found to be associated (at our predefined threshold of 1 × 10 −4 ) with a benign UC disease course. The rs11742570 variant on chromosome 5 was the one with the greatest association to benign disease although the association did not reach the predefined significant threshold. Given the modest power of our study, the findings suggested on the exploratory analysis merit extension to larger discovery cohorts. Abstract : Article first published online 26 August 2016.